2001
DOI: 10.1148/radiology.218.3.r01fe27848
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous versus Pyogenic Arthritis: MR Imaging Evaluation

Abstract: MR imaging of bone abnormalities, extraarticular lesions, and associated abscesses provides useful information in the differentiation of tuberculous arthritis and pyogenic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 21 publications
1
50
0
3
Order By: Relevance
“…This increased thickness was asymmetrical and it was most prominent in the medial and lateral aspects of the head with almost no thickening superiorly. These similar findings were also seen by Jaramillo D et al 12 (In 59% of cases) and by Rush BH et al 13 (In 70% of cases). There were two cases of slipped capital femoral epiphysis out of which both show slip of epiphysis and one show oedema involving the epiphysis.…”
Section: Abscess Wallsupporting
confidence: 85%
“…This increased thickness was asymmetrical and it was most prominent in the medial and lateral aspects of the head with almost no thickening superiorly. These similar findings were also seen by Jaramillo D et al 12 (In 59% of cases) and by Rush BH et al 13 (In 70% of cases). There were two cases of slipped capital femoral epiphysis out of which both show slip of epiphysis and one show oedema involving the epiphysis.…”
Section: Abscess Wallsupporting
confidence: 85%
“…This tubercular excavation is distinct from the fronts of resorption noted in erosive spondyloarthropathy, which actually disrupt the joint (subchondral) surface (Rothschild and Martin 1993;Rothschild and Woods 1991). Zones (rather than fronts) of resorption have been related to tuberculosis in humans (Hershkovitz et al 1998;Hong et al 2001;Rothschild and Martin 1993) and documented as Mycobacterium tuberculosis by DNA extraction in Pleistocene bison (Rothschild et al 2001). The characteristic erosions of tuberculosis are also distinguishable from rheumatoid arthritis and spondyloarthropathy on the basis of location.…”
Section: Methodsmentioning
confidence: 93%
“…However, MR showed features of marrow edema, subchondral bone involvement and joint effusion and together with clinical and lab investigations a definite diagnosis could be reached. Jung AH et al [10] and Sung Hwan Hong et al [11] in their studies on MR imaging features of inflammatory and infective conditions of the hip joint have described similar features that differentiate tubercular from pyogenic and rheumatoid arthritis.Midiri M et al [12] in their study of patients with infective conditions found that MR findings in this group are usually non specific but when put together with clinical and laboratory findings allows early and specific diagnosis, an observation similar to our study. The next common etiology of hip pain in our study was osteoarthritis (9 cases).…”
Section: Discussionmentioning
confidence: 95%